Portable autonomous solar power plant for individual use - Toshov, Javoxir; Saitov, Elyor (E3S web of conferences, 2019)
Development and design of low power mobile and inexpensive solar stations are important for farmers, individuals, geologists and trotters. The most important aspect is ensuring reliability of units in times of transportation, convenience and operational ease as well as minimum dimensions, low price. All the above will ensure large-scale implementation of solar stations in various applications and utilizations.